Piano Sonata no. 21 in C major, op. 53 (Kuntze) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Amsterdam; S. Kuntze; Netherlands)
Early edition of the Piano Sonata no. 21 in C major, op. 53, published by Kuntze